Diagnóstico clínico y tratamiento 2021 - Papadakis, Maxine A.; McPhee, Stephen J.; Rabow, Michael W. (McGraw-Hill's AccessMedicina., 2020)
Current Medical Diagnosis and Treatment 2021 (Clinical diagnosis and treatment 2021) is the 60 .a edition of this reference in a single source for physicians in both hospital and outpatient institutions. The book outlines the practical features of clinical diagnosis and patient management in all fields of internal medicine and in specialties of interest to general practitioners and subspecialists who provide general care.